Enantioselective Homocrotylboration of Aliphatic Aldehydes - Lin, Hongkun (2012)
A practical route to optically pure syn-homocrotylation reagents is described, including highly diastereo-and enantioselective preparation of numerous syn-homocrotyl products, as well as several matched mismatched pairs. NMR experiments suggest that the active homocrotylating species is a cyclopropylcarbinyldichloroborane generated by chloride exchange from the PhBCl(2) activator. Computational studies support the intermediacy of chloroboranes, and suggest that homoal-lyl/homocrotyl transfers occur through Zimmerman-Traxler transition states.